2019
DOI: 10.1063/1674-0068/cjcp1811254
|View full text |Cite
|
Sign up to set email alerts
|

Infrared photodissociation spectroscopic and theoretical study of the HC2nO+ (n=3−6) cations

Abstract: The carbon chain cations, HC2nO+ (n=3−6) are produced via a pulsed laser vaporization supersonic expansion ion source in the gas phase. Their infrared spectra are measured via mass-selected infrared photodissociation spectroscopy of the CO “tagged” [HC2nO·CO]+ cation complexes in 1600–3500 cm−1 frequency range. The geometric and electronic structures of the [HC2nO·CO]+ complexes and the core HC2nO+ (n=3−6) cations are determined with the aid of density functional theory calculations. These HC2nO+(n=3−6) ions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Indeed, the CO group imposes a considerable constraint on the photostability of oxygenated carbocations in the ISM compared to hydrocarbons, Chen et al (2018) with cumulenic-type structures such as H 2 C 2𝑛+1 O + and OC 2𝑛+1 O + (with 𝑛 = 2, 3, ...) being more stable than polyynic-type structures (Hardy et al 2016). Combined experimental studies of infrared (IR) photodissociation spectroscopy and theoretical modelling (Jin et al 2017;Li et al 2019) have shown that HC 2𝑛+1 O + and HC 2𝑛 O + (𝑛 = 3 − 6) possess a polyyne-like carbon chain structure with closed-shell singlet ground states and cumulene-like carbon chain structures with triplet ground states, respectively. Additionally, these studies have provided a preparative method of gaseous oxygenated carbon chains using laser vaporization of a graphite target in expansion of helium seeded with a mixture of CO, H 2 , and C 2 H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the CO group imposes a considerable constraint on the photostability of oxygenated carbocations in the ISM compared to hydrocarbons, Chen et al (2018) with cumulenic-type structures such as H 2 C 2𝑛+1 O + and OC 2𝑛+1 O + (with 𝑛 = 2, 3, ...) being more stable than polyynic-type structures (Hardy et al 2016). Combined experimental studies of infrared (IR) photodissociation spectroscopy and theoretical modelling (Jin et al 2017;Li et al 2019) have shown that HC 2𝑛+1 O + and HC 2𝑛 O + (𝑛 = 3 − 6) possess a polyyne-like carbon chain structure with closed-shell singlet ground states and cumulene-like carbon chain structures with triplet ground states, respectively. Additionally, these studies have provided a preparative method of gaseous oxygenated carbon chains using laser vaporization of a graphite target in expansion of helium seeded with a mixture of CO, H 2 , and C 2 H 2 .…”
Section: Introductionmentioning
confidence: 99%